1992
DOI: 10.1128/jb.174.18.5988-5993.1992
|View full text |Cite
|
Sign up to set email alerts
|

Directed mutagenesis in an asporogenous methylotrophic yeast: cloning, sequencing, and one-step gene disruption of the 3-isopropylmalate dehydrogenase gene (LEU2) of Candida boidinii to derive doubly auxotrophic marker strains

Abstract: A model system for one-step gene disruption for an asporogenous methylotrophic yeast, Candida boidinii, is described. In this system, the 3-isopropylmalate dehydrogenase gene (C. boidinii LEU2) was selected as the target gene for disruption to derive new host strains for transformation. First, the C. boidinii LEU2 gene was cloned, and its complete nucleotide sequence was determined. Next, the LEU2 disruption vectors, which had the C. boidinii UR43 gene as the selectable marker, were constructed. Of the Ura+ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…pFGHD was digested with SacI and XhoI, and then used for the transformation of C. boidinii strain TK62. The FGH1-disrupted (fgh1D) strain was caused to revert to uracil auxotrophy after 5-fluoroorotic acid selection, yielding the fgh1Dura3 strain, by our previously described procedure (Sakai & Tani, 1992). The gene disruption and loss of URA3 were confirmed by genomic Southern analysis using XbaI-digested genomic DNA from each transformant with the 1?0 kb EcoRV-NdeI fragment harbouring the 59-flanking region of FGH1 as the probe (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…pFGHD was digested with SacI and XhoI, and then used for the transformation of C. boidinii strain TK62. The FGH1-disrupted (fgh1D) strain was caused to revert to uracil auxotrophy after 5-fluoroorotic acid selection, yielding the fgh1Dura3 strain, by our previously described procedure (Sakai & Tani, 1992). The gene disruption and loss of URA3 were confirmed by genomic Southern analysis using XbaI-digested genomic DNA from each transformant with the 1?0 kb EcoRV-NdeI fragment harbouring the 59-flanking region of FGH1 as the probe (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…pFGH was digested with NdeI and NcoI to remove an approximately 143 bp fragment of the partial coding sequence of FGH1. The remaining linearized plasmid and the 4?6 kb SacI-XhoI fragment of C. boidinii URA3 DNA from pSPR (Sakai & Tani, 1992) were blunt-ended with T4 DNA polymerase and then ligated, yielding FGH1 disruption vector pFGHD. pFGHD had C. boidinii URA3 DNA as a selectable marker and truncated FGH1-flanking sequences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining fragment was gel purified, blunted with T4 DNA polymerase, and ligated to the SacI-XhoI fragment of pSPR (C. boidinii URA3 gene having repeated sequence at the 5Ј-and 3Ј-franking regions) (23). The ligation reaction generated the C. boidinii PMP20 disruption vector pD20SPR.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for using CbPmp20 in the methylotrophic yeast C. boidinii are as follows: 1) Because CbPmp20 is specifically induced in methanol-containing medium and is exclusively localized within peroxisomes, we can specify the function of CbPmp20 within methanol-induced peroxisomes (17,22). 2) The molecular genetics (23,24) and organelle fractionation techniques (25,26) have been well established with C. boidinii. Through this study we have demonstrated that the Pmp20-antioxidant system indeed functions within peroxisomes as GPX and that the antioxidant function of CbPmp20 is biochemically and physiologically distinct from that of peroxisomal catalase.…”
mentioning
confidence: 99%